Microbial-algal community changes during the latest Permian ecological crisis: Evidence from lipid biomarkers at Cili, South China - Luo, G.; Wang, Y.; Grice, Kliti; Kershaw, S.; Algeo, T.; Ruan, X.; Yang, H.; Jia, C.; Xie, S. (Elsevier Science BV, 2013)
Microbialites flourished globally immediately following the latest Permian mass extinction. In this study, lipid biomarker records were analyzed in the Cili section (Hunan Province, South China) in order to determine the types of microbes involved in microbialite formation and their response to contemporaneous environmental changes. Various biomarkers were identified in the aliphatic and aromatic fractions using gas chromatography (GC) and GC–mass spectrometry (GC–MS). Low abundance of steranes in the microbialite layer suggests that it did not contain large amounts of algae, in striking contrast to the abundant algal fossils and algal-derived steranes present in the underlying (pre-crisis) skeletal limestone. Although pristine/phytane (Pr/Ph) ratios increased in the microbialite layer, covariation of Pr/Ph with the ratio of low- to high-molecular-weight n-alkanes (C20 −/C20 +) suggests that the former proxy was controlled by microbial (particularly cyanobacterial) inputs rather than by redox conditions.The microbialite also yielded low ratios of hopanes to short-chain n-alkanes (HP/Lalk) and high abundances of C21n-alkylcyclohexane, indicating that, in addition to cyanobacteria, anaerobic bacteria, archaea, and possibly acritarchs flourished in the aftermath of the marine extinction event. The upper part of the thinly bedded micritic limestone overlying the microbialite exhibits a bimodal distribution of n-alkanes as well as increased abundances of extended tricyclic terpanes and steranes, suggesting a return of habitable shallow-marine conditions for eukaryotic algae several hundred thousand years after the latest Permian mass extinction. Increases in the dibenzofuran ratio (i.e., DBF/(DBF + DBT + F)) and in the coronene to phenanthrene ratio (Cor/P) in the skeletal limestone immediately below the microbialite are evidence of enhanced soil erosion rates and wildfire intensity, marking the collapse of terrestrial ecosystems. The terrestrial crisis thus slightly preceded the marine biotic crisis in the South China region, to which it may have been a major contributing factor.